ANALYSIS OF ISSUING ACTIVITY OF COMMERCIAL BANKS OF THE REPUBLIC OF UZBEKISTAN IN THE SECURITIES MARKET (Marketing Journal, 2025)
This article analyzes the emission activities of commercial banks of the Republic of Uzbekistan in the securities market. The study examines the role of banks as issuers, investors, and investment intermediaries, and analyzes the legislative framework and the level of market infrastructure development. Based on national and international practices, the specific features of commercial banksʼ emission activities are identified, existing issues are highlighted, and recommendations for improvement are developed . The findings provide a basis for practical recommendations aimed at further developing the countryʼs financial market and enhancing banksʼ activity.
Keywords: commercial bank; securities market; emission activity; investment activity; financial market; legislation; banking operations. 353